An introduction of Islamic value-based productivity framework - Mohammad Rosli, Nurul Ain; Md Dahlal, Norazilawati; Elgharbawy, Amal A.M. (ARC Publications, 2021)
Productivity is commonly used in measuring the efficiency of production. Both conventional and Islamic perspectives come with the same general meaning of productivity and the importance of the values also take place in both perspectives. The values of the conventional productivity concept measured by using tangible indicators such as skills and knowledge of workers. While in the Islamic perspective, the values of productivity are measured beyond the tangible indicators; and show that it is holistic and comprehensive. Even though the interest in values is expanding, the discussion only continues conceptually, narrowly focusing on the list of Islamic values. In addition, no empirical evidence has been recorded as far as the researchers are concerned, which scientifically explains the application of Islamic values, specifically in productivity. Therefore, this study aims to introduce an Islamic value-based productivity framework from the identification and interpretation of selected Quranic verses related to productivity. By applying a descriptive research design, this study has used the content analysis method. The findings showed that the Islamic value-based productivity framework consists of four main indicators; faith, intention, time: as inputs, and job satisfaction as outputs. The values extracted from these indicators consist of eight values which are Ihsan (Excellence), Itqan, Taqwa, Shukr (Gratitude), Istiqamah, Sabr (Patience), Tawakkul and Barakah (Divine Blessing).